STUDI PRAKTIK WAKAF DIBALIK GADAI DI MASJID MA’MUR TIGA BATUR KECAMATAN SUNGAI TARAB KABUPATEN TANAH DATAR - Rahma Putri; Eficandra Eficandra; Amri Effendi (JISRAH: Jurnal Integrasi Ilmu Syariah, 2023)
This study examines the Wakaf Behind Pawn Practice Reviewed From the Perspective of Sharia Economic Law ( Case Study at the Masjid Ma'mur Tiga Batur, Sungai Tarab District, Tanah Datar Regency). The problem is how wakaf practice is behind pawnbroking, what are the driving factors for wakaf practice behind pawnbroking and how sharia economic law views wakaf practice behind pawnbroking at the Ma'mur Tiga Batur Mosque, Sungai Tarab District, Tanah Datar Regency. This type of research is field research with qualitative descriptive methods with data collection techniques being interviews and documentation. The practice of waqf behind pawnbrokers that are carried out by pawnbrokers starts with the pawnbroker and the pawnbroker and then the pawnbroker manages, utilizes, and there are results. Factors driving the practice of wakaf behind pawnshops include the factors driving the worship and environmental factors of local parties or community leaders and scholars who explain pawnshops and waqf, thus making the wakif interested in. Wakaf is basically allowed from pawnshops, but it is not recommended because the source of the wakaf comes from everything that is not allowed, namely the use of pawnshops by pawnbrokers. While the ransom value waqf is fully allowed